A study on partnering and strategic alliances in the shipping industry - Lee, Kenneth Ensong. (2012)
The aim of this report is to study partnering and alliances in the shipping industry. The report will examine in detail the reasons and factors affecting a partnering and alliances in the shipping industry. 3 main sectors of the shipping industry are selected for the purpose of this report, namely the bulk, container and offshore sectors will be covered. Firstly, the reasons as to why strategic alliances are so popular will be discussed. Moving on the report will discuss the success and failure factors affecting a strategic alliance in the shipping industry. Next would be on the future prospects of such cooperation and lastly it will show how to better manage the pitfalls and issues affecting the successfulness of an alliance.